EXPLORING NARRATIVE DEVICE IN AMERICAN POP CULTURE: A CASE STUDY OF EX MACHINA (2014) - Lestari, Siwi; Nurhamidah, Idha; Muna, Nailil; Permtasari, Riana (Jurnal Ilmiah Sultan Agung, 2025)
Language is a crucial aspect of life for communicating, expressing feelings, and building relationships with others. In literature, language and context are interconnected; pragmatics helps reveal the hidden meaning behind the text. In the context of pragmatic, films not only show futuristic narratives, but it also shows how dialogue and interaction between characters are used to convey deeper meaning. The language that is often used in a literary work is usually a style of figurative language. This research refers to Laurence Perrine’s theory on identifying and analyzing the types of figurative language and exploring their functions in supporting narrative meaning and characterization in the film Ex Machina. This research uses descriptive qualitative method. The primary data used in this study is the film Ex Machina and secondary data were obtained from articles, journals, and previous study. Data collection technique is carried out by watching the movie, reading movie script and then, analyzed to find types and function of each figurative language used. From the research that has been done it can be concluded that the types of figurative language found in the Ex Machina film are Allegory, Hyperbole, Irony, Metaphor, Metonymy, Paradox, Personification, Simile, Symbol, and Synecdoche which are more dominantly appearing are metaphor and hyperbole. Meanwhile, the functions found in figurative language in the Ex Machina film not only function as aesthetic decoration, but also to provide imaginative pleasure, add emotional intensity, create meaning in a short compass, and to provide additional meaning related to philosophical issues such as artificial consciousness and human identity. The Ex Machina film raises the theme of artificial intelligence, consciousness, and ethics in creating technology. Keywords: Pragmatic, Figurative Language, Ex Machina Movie.